On dissipative MHD mixed convection boundary layer flow of Jeffrey fluid over an inclined stretching sheet with nanoparticles: Buongiorno model - Mohd Zokri, Syazwani; Arifin, Nur Syamilah; Mohd Kasim, Abdul Rahman; Mohammad, Nurul Farahain; Salleh, Mohd Zuki (VINCA Institute of Nuclear Sciences, 2018)
Present paper utilizes a combination of non-Newtonian fluid model (Jeffrey fluid) with Buongiorno model (nanofluid). The Jeffery fluid, which is regarded as a base fluid, together with suspended nanoparticles are examined over an inclined stretching sheet with the amalgamated impacts of mixed convection and viscous dissipation. The mathematical formulation of this model is done by choosing the appropriate similarity variables for the aim to reduce the complexity of governing partial differential equations. The Runge-Kutta-Fehlberg (RKF45) method is then applied to the resulting of nonlinear ordinary differential equations to generate numerical results for highlighting the impact of emerging parameters towards specified distributions. Both the graphical and tabular representations of vital engineering physical quantities are also shown and deliberated. For the increase of Eckert number, thermophoresis diffusion and Brownian motion parameters, the elevation of temperature profiles is observed. Besides, the thermophoresis diffusion parameter tends to accelerate the nanoparticle concentration profile while Brownian motion parameter displays the opposite behavior